2015
DOI: 10.5606/archrheumatol.2015.5122
|View full text |Cite
|
Sign up to set email alerts
|

Disease Activity (Rheumatoid Arthritis Disease Activity Index-5) in Patients With Rheumatoid Arthritis and its Association With Quality of Life, Pain, Fatigue, and Functional and Psychological Status

Abstract: Objectives: This study aims to determine disease activity in patients with rheumatoid arthritis by Rheumatoid Arthritis Disease Activity Index-5 (RADAI-5), and to evaluate its association with the quality of life, pain, fatigue, and functional and psychological status. Patients and methods: A total of 170 rheumatoid arthritis patients (30 males, 140 females; mean age 55.2±11.3 years; range 28 to 82 years) were included in the study. Quality of life was evaluated by using Rheumatoid Arthritis Quality of Life Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
6
9
0
3
Order By: Relevance
“…The present study results of RAQOL questionnaire on patients with RA revealed that DAS-28 has a significant strong positive correlation with QOL of patients with RA (r=0.70, P=0.00); most patients on remission or with low disease activity showed good QOL and low RAQOL score, and others with high disease activity showed high RAQOL score and bad QOL. This is consistent with a study which reported that disease activity in RA had a negative effect on QOL, which was measured with Rheumatoid Arthritis Quality of Life Scale, a RA-specific measure [29]. Moreover, this is consistent with another study that was conducted on 79 patients with RA in Colombia, where they evaluated QOL by using Quality of life-Rheumatoid Arthritis Scale [30] and demonstrated that RA activity significantly influenced QOL.…”
Section: Discussionsupporting
confidence: 91%
“…The present study results of RAQOL questionnaire on patients with RA revealed that DAS-28 has a significant strong positive correlation with QOL of patients with RA (r=0.70, P=0.00); most patients on remission or with low disease activity showed good QOL and low RAQOL score, and others with high disease activity showed high RAQOL score and bad QOL. This is consistent with a study which reported that disease activity in RA had a negative effect on QOL, which was measured with Rheumatoid Arthritis Quality of Life Scale, a RA-specific measure [29]. Moreover, this is consistent with another study that was conducted on 79 patients with RA in Colombia, where they evaluated QOL by using Quality of life-Rheumatoid Arthritis Scale [30] and demonstrated that RA activity significantly influenced QOL.…”
Section: Discussionsupporting
confidence: 91%
“…5 Penelitian yang dilakukan oleh Sunar, dkk. 6 menyatakan bahwa terdapat hubungan yang signifikan antara derajat aktivitas penyakit AR dengan kejadian depresi. Selain itu, depresi pada pasien AR juga merupakan faktor risiko independen terjadinya penyakit kardiovaskuler dan infark miokard, kecenderungan bunuh diri, dan kematian, bahkan setelah derajat aktivitas AR, disabilitas, dan nyerinya telah teratasi.…”
Section: Pendahuluanunclassified
“…Penelitian serupa yang telah dilakukan sebelumnya mendapatkan hasil yang sama, yaitu terdapat hubungan yang bermakna antara derajat aktivitas penyakit dengan depresi. 2,3,6 Ras dan faktor budaya tidak dapat dipisahkan dari terjadinya depresi. Penelitian oleh Imran, dkk.…”
Section: Diskusiunclassified
See 1 more Smart Citation
“…Comorbid depression in RA is associated with a worsening of disease activity and severity, 10 and has a significant impact on patient quality of life. 11 Recent studies have shown a positive correlation between pain and depressive symptoms in RA.…”
Section: Introductionmentioning
confidence: 99%